Potentials of Iron Oxide Nanoparticles (Fe3O4): As Antioxidant and Alternative Therapeutic Agent Against Common Multidrug-Resistant Microbial Species - Muhammad, Farah; Hussein, Nehaia Nima; Sulaiman, Ghassan Mohammad (Iraqi Journal of Science, 2023)
For the treatment of pathogenic bacterial infections, multidrug resistance (MDR) has become a major issue. The use of nanoparticles is a promising strategy for combating medication resistance in a variety of pathogens that cause deadly diseases. The goal of our research was to extract multidrug-resistant bacteria from wound infections and then use iron oxide nanoparticles (Fe3O4) as alternative therapeutic agents in vitro. Gram staining, morphological attributes evaluation, and biochemical testing were used to assess the microbes. The Kirby-Bauer disk diffusion method was used to test MDR-bacterial strains against several antibiotics; the majority of these isolates were resistant to ceftazidime, amoxicillin, Gentamicin, and tetracycline. the iron oxide nanoparticles were produced by the co-precipitation method and were confirmed by changing the color to dark black as well as the Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM) analysis that shows the shape and average size between (29.03-56.54) nm. The highest effect of iron oxide nanoparticles (Fe3O4) on the growth of Proteus.mirabilis (P.mirabilis) was as it was found that the average diameter of the inhibition zone was 22.66±1.15 mm, followed by Staphylococcus.epidermidis (S.epidermidis), Acinetobacter.baumannii (A.baumannii) with the average diameter of the inhibitory zone it was 21.66±1.52 mm, 20.33±1.53 mm respectively, and Candida.albicans (C.albicans) was 18.33±1.15 mm at 100 µgmL-1 (stock). The synthesized iron oxide nanoparticles (Fe3O4) are used to capture rapidly microbes under the magnetic field effect. The antioxidant activity DPPH of the iron oxide nanoparticles (Fe3O4) showed 29.3%, 42.2%, 58.6%, 67.4%, and 74 % at a concentration (6.25, 12.5, 25, 50, 100) µgmL-1 respectively, it demonstrated that the scavenging percentage increase with increasing the iron oxide nanoparticles (Fe3O4) concentrations.